PENGALAMAN-PENGALAMAN TERBAIK DALAM MELAKSANAKAN PENDEKATAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR: KAJIAN PRAKTIK REFLEKTIF GURU - Novita Wulandari; Eko Kuntarto; Desy Rosmalinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objectives of this study include: (1) how teachers implement a differentiated learning approach in elementary schools; (2) what are the best experiences of teachers in implementing a differentiated learning approach in elementary schools; (3) what are the factors that support and hinder the implementation of differentiated learning that teachers do.The research method used is qualitative with a phenomenological approach. The research subjects were teachers from SDN 182/I Hutan Lindung, SDN TRIO SRIDADI, SDN 70/I Simpang Terusan, SDN 95/I Olak, and SDN 32/I Pematang Lalang. Data were collected through observation, interviews, and documentation. The analysis techniques involved data reduction, data presentation, and drawing conclusions. The results show that teachers have implemented differentiated learning by mapping students’ readiness, interests, and learning styles through observation, questionnaires, and informal conversations. Lesson plans were designed with differentiation in content, process, and product. Teachers’ best practices are reflected in their flexibility and sensitivity in responding to student diversity, creating a conducive and interactive learning environment. Supporting factors include school support, availability of media, and teacher creativity, while the inhibiting factors involve lack of parental support, significant differences in student readiness, limited learning resources, and insufficient time and student profile data.